A durability- based design approach for structural applications with advanced cement-based materials - Francesco Soave; Liberato Ferrara (Case Studies in Construction Materials)
The poor durability of existing reinforced concrete structures has shown that current approaches to tackle this issue in the overall structural design framework fail to guarantee an adequate level of safety for structures over the intended service life. In this paper, the prescriptive approach recommended by national and international codes, which guides mix-design and minimum cover thickness, is replaced by a performance design based on durability. This method allows to define the structural performance evolution over time and to schedule, as a consequence of the possible attainment of limit states, ordinary maintenance campaigns aimed at restoring the structural performance at an adequate and acceptable level. A geothermal water collection tank has been considered as a case study. This structure can benefit from a performance-based durability-design tailored to the use of high-performance construction materials since the retaining tank walls are exposed to a highly aggressive environment: both XA and XD exposure classes, as per EN206 can be considered since the water is characterized by high concentration of chlorides and sulphates. In the literature, different models are available that can describe the mechanisms of degradation associated with the aforesaid exposure conditions. The first design phase involved the use of the prescriptive approach for ordinary reinforced concrete. The effectiveness of this design has been evaluated through the study of the effects determined by the degradation phenomena. Later, a signature material concept, named UHDC (Ultra High Durability Concrete developed in the framework of the Horizon2020 ReSHEALience project and meant as an evolution of the UHPC) is introduced. This material concept, which is based on enhanced durability in the cracked state and self-healing functionalities, can lead to new design paradigms both from the mechanical and durability point of view. In this framework, a performance based durability design approach is proposed, which, through experimentally calibrated time-evolution trends for the material performance and design constitutive laws, defines the evolution, over the intended service life, of the structural performance indicators and the consequently needed, if any, maintenance interventions. This kind of design approach has to be intended as prodromal and necessary for a solid assessment of the sustainability of structural applications with advanced cement-based materials which goes beyond the mere CO2 footprint of a unit material volume and encompasses the whole service life and the overall structural service scenario.